Cabaran komunikasi dalam pengajaran Pendidikan Islam kepada murid kurang upaya pendengaran - Izuli Dzulkifli,; Asmawati Suhid,; Fathiyah Mohd Fakhruddin,; Nor Aniza Ahmad, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Pupils with hearing impairment have their own form of communication. They also get the opportunity to learn Islamic Education subject at the primary level in the Special Primary Schools (SPK) and Special Education Integrated Programme (PPKI). Islamic Education subject has six main areas namely al-Quran, Akidah, Ibadah, Akhlak, Sirah and Jawi. Since the level of hearing and speech impairment of the pupils with special needs are limited, it is essential that the communication aspect in teaching should be taken into the teachers’ consideration. The objective of this study is to explain the method of communication used by the teachers as well as the challenges in communication during teaching Islamic Education subject to pupils with hearing impairment. This study utilized the qualitative approach in the form of a case study, using the interview technique and document analysis to obtain data. The findings showed there were inconsistencies in the teachers’ communication in delivering the Islamic Education subject to the pupils. Lack of proper codes or signs related to Islamic Education and lack of skills in using sign language are the reasons for inconsistencies in the teachers’ communication in delivering the subject to the pupils.